PARTAI POLITIK DAN INKONSISTENSI KOALISI DALAM PEMILU 2014 DAN 2019 - Kunkunrat .; Ade Priangani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2019)
Interesting events in the last 2 (two) elections, where there is a phenomenon of political parties contesting in the 2014 and 2019 elections trying to create an election that puts forward checks and balances between government support parties and opposition parties in the form of coalitions. In the 2014 elections there was a Great Indonesian Coalition (KIH) government, consisting of PDI-P, Nasdem, PKB, Hanura and PKPI, and the opposition Red and White coalition (KMP), consisting of Gerindra, Golkar, PAN, PKS, PPP and the United Nations. It is hoped that the people will have checks and balances so that the minority government is controlled by a large opposition. But that hope vanished as Golkar, PAN and PPP joined the government, so the opposition was no longer helpless, because it only left Gerindra and PKS. The recurring incident in the 2019 election, in which the presidential election gave birth to 2 coalition supporters of Jokowi-Maruf Amien Coalition of Working Indonesia (PDI-P, Nasdem, PKB, Hanura, PKPI, Golkar, PPP, Perindo, PSI) and the Coalition supporting Prabowo-Sandiaga, named The Indonesian Coalition is just and prosperous (Gerindra, PKS, PAN, Democrat), it is very apparent that there is a desire from PAN and Democrats to be part of the government coalition, inconsistencies occur in coalition in Indonesia.